A Comparative Study of 3D Conformal Radiotherapy Versus Intensity Modulated Radiotherapy with Simultaneous Integrated Boost in Locally Advanced Head and Neck Cancer Patients - Sudhanshu, Shrenuka; Sharma, Neeti; Sinwer, Rajesh; Kumar, H.S.; Lal Jakhar, Shankar (Asian Pacific Journal of Cancer Care, 2025)
Introduction: Role of radiotherapy in comprehensive management of head and neck cancer for achieving tumor control and organ preservation is now well established and radiotherapy is routinely used as definitive or in the adjuvant setting after surgery, concurrently with chemotherapy or targeted agents. Development of linear accelerator with Multileaf Collimator (MLC) have revolutionized radiation delivery techniques, allowing conformal and Intensity Modulated Radiotherapy (IMRT) to deliver highly conformal sculpted radiation dose to a very complex structure with improved sparing of adjoining critical structures like salivary glands, spinal cord, eyes, and brainstem amounting to better therapeutic gain. Aim and Objective: This prospective study is to compare toxicity profile of IMRT-SIB with Three Dimensional Conformal Radiotherapy (3D CRT) in head and neck cancer. Materials and Methods: A total of 80 patients with proven head and neck cancer were included in the study. They underwent radiotherapy on Linac 2300 CD for 3D-CRT and TRUEBEAM SVC machine for the IMRT comprised of 40 patients in each arm. Patients received 66Gy/30 fractions, as radical treatment in the IMRT arm for 6 weeks and 66 Gy/33 fractions in the 3DCRT arm for 6.5 weeks from Monday to Friday. Results: The 3D-CRT group demonstrated significantly more acute toxic effects compared with the IMRT group in our analysis. Acute Grade 3 or greater toxic effects to the skin occurred in 7 of 40 (17.5%), patients in the 3D-CRT group compared with 3 of 40 (7.5%) patients in the IMRT group. Acute Grade 3 or greater toxic effects to the mucous membranes occurred in 15 of 40 (37.5%) patients in the 3D-CRT group and only 9 of 40 (22.5%) patients in the IMRT group. Statistically significant grade III dysphagia developed in 8 of 40 (20%) patients in 3D-CRT group compared with 4 of 40 (10%) patients in IMRT group, while significant grade II xerostomia developed after 6 month of treatment; 20 of 40 patients in 3D-CRT group (50%), compared with 13 of 40 (32.5%) patients in IMRT group. Conclusion: In our comparative study, IMRT was associated with a significantly lower incidence of Grade 3 or greater xerostomia, acute toxic effects to skin (dermatitis) and mucous membranes (mucositis) than 3DCRT. In addition, compared to 3D-CRT, IMRT had lower rates of feeding tube use during radiotherapy. Our analysis showed potentially less toxicity in patients treated with IMRT in comparison to 3D-CRT.